A Survey of Caudal Anaesthesia practice in an academic anaesthesia unit - Julius, Sepheu Letshokge (University of the Witwatersrand, Johannesburg, 2022)
Background Caudal blockade is a means of providing intra and postoperative analgesia and minimises the sympathetic stress response to abdominal and lower limb surgery. Clear anatomical landmarks and ease of performing the procedure make it one of the most commonly performed regional techniques in the paediatric population. Methods A prospective, contextual, descriptive study was conducted between 2020 and 2021 on anaesthetists working in an academic anaesthesia unit. Data was collected anonymously through a digital questionnaire and participation was voluntary. Results The study sample is made up of 40 consultants and career medical officers (27%), 87 registrars (61%), 15 medical officers (10.6%) and two community service medical officers (1.4%). Plain bupivacaine at 2.5mg/kg was found to be the local anaesthetic of choice. Most participants,90 (63.1%), did not use an adjunct in their caudal blocks, with the risk of excessive sedation and risk of postoperative apnoea being the most frequently cited reasons. Where an adjunct was used, the alpha-2 agonists; clonidine (64.5%) and dexmedetomidine (53.2%) were chosen. The majority,122 (85.1%), anaesthetists acquired consent specifically for caudal blocks. Potential complications of caudal blockade, the duration of analgesia and the technique of the caudal block were frequently discussed with patients and their caregivers when obtaining consent. Use of ultrasound is not in widespread practice, and block failure was reported by 91 (63.8%) participants. Paracetamol was the most regularly employed rescue analgesia. Conclusion This study found that the academic unit’s caudal blockade practice compared well with local and international literature. The use of adjuncts, ultrasound and caudal catheters is not a widespread practice, and clear guidelines may be beneficial in this regard. Use of standardised informed consent protocols may improve the patient and caregiver experience
A research report submitted in the partial fulfillment of the requirements for the degree of Master of Medicine in the branch of Anaesthesiology to the Faculty of Health Sciences, School of Clinical Medicine, University of the Witwatersrand, Johannesburg, 2022
Keywords: paediatric; Anaesthetic practise; Analgesia; Caudal block; SDG-3: Good health and well-being